2004
DOI: 10.1021/cg0497750
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Monitoring of the Impact of Liquid−Liquid Phase Separation on Drug Crystallization by Seeding

Abstract: the impact of a liquid-liquid-phase separation (LLPS) or demixing on solution crystallization in quiescent medium of a pharmaceutical compound, C 35 H 41 Cl 2 N 3 O 2 , in an ethanol/water mixture was presented. In this contribution, drug crystallization experiments by seeding are monitored by in situ turbidity, focused beam reflectance measurement, and video microscopy. Two cases are studied: in the first case for seeding experiments in the metastable zone for nucleation and outside the demixion zone we obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 21 publications
(40 reference statements)
4
56
0
1
Order By: Relevance
“…In the cases of lysozyme and BPTI, the metastable liquid phase impedes the nucleation of the solid phase, which was also observed for some organic molecules. 44,45 Note that recently, in an extremely interesting paper from Vivarès et al 46 on the crystallization of glucose isomerase in the presence of a metastable LLPS observed by confocal scanning fluorescence microscopy, it has been shown that nucleation and crystal growth mainly occurred inside the dense phase. Finally, we propose the following practical rule for crystallization: when we observe a demixion, it is bound to be metastable with respect to crystallization and therefore the best crystallization temperature is T, with T e > T g T L-L , where T e is the crystal-liquid equilibrium temperature.…”
Section: Bpti Nucleation and Llpsmentioning
confidence: 99%
“…In the cases of lysozyme and BPTI, the metastable liquid phase impedes the nucleation of the solid phase, which was also observed for some organic molecules. 44,45 Note that recently, in an extremely interesting paper from Vivarès et al 46 on the crystallization of glucose isomerase in the presence of a metastable LLPS observed by confocal scanning fluorescence microscopy, it has been shown that nucleation and crystal growth mainly occurred inside the dense phase. Finally, we propose the following practical rule for crystallization: when we observe a demixion, it is bound to be metastable with respect to crystallization and therefore the best crystallization temperature is T, with T e > T g T L-L , where T e is the crystal-liquid equilibrium temperature.…”
Section: Bpti Nucleation and Llpsmentioning
confidence: 99%
“…Liquid-liquid equilibrium data have been investigated for some "anti-solvent" crystallization experiments [2,3], spherical crystallizations using a three solvents system [4,5], oiling out phenomena [6][7][8][9][10] and reverse addition processes [11]. The LLPS makes crystallization difficult in protein systems [12,13], prevents drug nucleation [14][15][16], and hinders nucleation in crystallization of droplets [17]. Lack of phase diagram data for crystallization processes with LLPS makes it difficult to understand, design and control the process.…”
Section: Introductionmentioning
confidence: 99%
“…Oiling out has firstly been detected for solutions of large molecules like proteins and polymers [1][2][3][4][5][6][7] due to the different molecular sizes of polymer and solvent. Recently, experimental studies proved the existence of oiling out also for mixtures containing organic substances with low molecular weights [8][9][10][11][12][13]. However, none of the literature references reported the feasibility of modeling or even predicting the oiling-out behavior.…”
Section: Introductionmentioning
confidence: 99%